Melastoma malabathricum crude extract causes damage to biofilm formation of Streptococcus mutans - Hanafiah, RM; Noor, WSAWM; Yaacob, WA; Ramli, SNRM; Ibrahim, N (Elsevier Science Bv, 2024)
Indexed by WOS